MONOAMINERGIC NEUROTRANSMISSION ACTIVITY MODULATION COULD ACTIVATE THE COMPENSATORY-ADAPTATION CAPACITIES IN CONDITIONS OF EXPERIMENTAL BRAIN TRAUMA - Vastyanov, R.S.; Stoyanov, O.M.; Dobrovolskyi, V.V.; Plakida, O.L.; Talalayev, K.O.; Babienko, V.V.; Stepanov, G.F. (World of Medicine and Biology, 2024)
The purpose of the study was to evaluate the changes in motor and muscle activity in the dynamics of the post-traumatic period in conditions of serotonin-, dopamine- and noradrenergic neurotransmitter systems activity modulation. Experimental trials were performed on a model of brain trauma of medium severity. Prior to this, measures were taken to activate and suppress the activity of serotonin-, dopamine- and noradrenergic neurotransmitter systems in animals. The peculiarities of motor and muscle activity were determined 1, 7, 14, 21, 28 and 35 days after the brain trauma reproduction with rats’ activity of monoaminergic neurotransmitter systems modulation of rats, the features of motor and muscle activity were determined. The data obtained confirm the motor and muscle disorders development in rats with brain trauma medium severity starting from the 1st day till the 35th day of the post-traumatic period. The post-traumatic period is characterized by evident neurological deficits and motor and muscle disorders which are manifested by muscle weakness, the inability to keep and maintain a natural position, as well as the inability to perform synchronous coordinated movements. Revealed motor and muscle dysfunctions are persistent and have their maximal expression during the first 14 days of the post-traumatic period. Serotoninergic and dopaminergic neurotransmitter systems activation in rats with brain trauma causes the motor and muscle functions of the body restoration and normalization. The authors stressed that serotoninergic and dopaminergic neurotransmission pathogenetic importance in conditions of traumatic brain damage should be taken into account when compiling and determining the clinical efficacy of complex pathogenetic therapy schemes for patients with brain trauma.